2018
DOI: 10.1007/s11060-018-03009-7
|View full text |Cite
|
Sign up to set email alerts
|

Mebendazole and radiation in combination increase survival through anticancer mechanisms in an intracranial rodent model of malignant meningioma

Abstract: Purpose Meningiomas are a frequent tumor of the central nervous system. Although mostly benign, approximately 5% present as atypical or malignant tumors. Treatments for atypical meningiomas include gross total resection and radiotherapy, but about 33% of patients have recurrent tumors, sometimes as a higher grade. Recently, the brain penetrant anthelmintic drug, mebendazole, has shown promise as an anticancer agent in rodent models of glioblastoma and medulloblastoma. Methods The half maximal inhibitory conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Supplementary Table 1 ( 4 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 ) summarizes the antitumorigenicity of benzimidazole anthelmintics on cancer cell lines. Benzimidazole anthelmintics inhibit the progression of cancer through a variety of mechanisms.…”
Section: Antitumorigenic Effects Of Benzimidazole Anthelmintics In Camentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary Table 1 ( 4 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 ) summarizes the antitumorigenicity of benzimidazole anthelmintics on cancer cell lines. Benzimidazole anthelmintics inhibit the progression of cancer through a variety of mechanisms.…”
Section: Antitumorigenic Effects Of Benzimidazole Anthelmintics In Camentioning
confidence: 99%
“…We summarized the antitumorigenicity of benzimidazole anthelmintics in animal tumor models ( Supplementary Table 2 ) ( 4 8 11 12 13 14 15 16 17 20 27 28 29 30 34 35 36 37 39 45 47 51 52 54 55 56 57 61 63 64 65 66 69 70 71 74 75 76 78 79 80 92 93 94 ). Benzimidazole anthelmintics have been shown to inhibit the tumor growth in animals, which have been well-tolerated without significant side effects during the experimental period.…”
Section: Antitumorigenic Effects Of Benzimidazole Anthelmintics In Anmentioning
confidence: 99%
“…Meningioma is a usually benign tumor of the central nervous system, but approximately 5% of the cases are represented by a malignant variant characterized by dismal prognosis [54]. Skibinski et al described the antitumoral effect of MBZ on malignant meningioma combined with IR [55]. In vitro, MBZ showed antiproliferative effects on several meningioma lines with IC 50s in the 0.26–0.42 μM range.…”
Section: Preclinical Evidence Of Anticancer Activitymentioning
confidence: 99%
“…Our methodology thus identified 17 novel putative targets of MBZ. We also observed that 12 of the 21 predicted targets are significantly overexpressed in GBM as compared to normal brain tissue, which may explain why MBZ is particularly effective against brain tumors [11,13,14,17,31].…”
Section: Discussionmentioning
confidence: 64%